Efficacy and Safety of GLP-1 Receptor Agonists as Adjuvant Pharmacotherapy After Bariatric Surgery: A Narrative Review - Natanael Sinaga; Lionel Sirait (Indonesian Journal Publisher, 2026)
Bariatric surgery remains the most effective long-term intervention for severe obesity, yet many patients experience inadequate weight loss or post-operative weight regain. GLP-1 receptor agonists (GLP-1 RAs) have emerged as promising adjuvant options through complementary mechanisms of appetite suppression and glycemic regulation.Aim: To evaluate the efficacy and safety of GLP-1 RAs as adjuvant pharmacotherapy in adult post-bariatric surgery patients. Methods, A systematic PubMed/MEDLINE search was conducted from January 2015 to January 2026. Eligible studies included adult post-bariatric patients receiving any GLP-1 RA with reported weight, glycemic, or safety outcomes. Case reports, animal studies, and review articles were excluded. Results, Eleven studies comprising 873 patients were included. GLP-1 RAs consistently demonstrated clinically meaningful weight reduction across all agents, with total body weight loss ranging from 5% to over 15% depending on agent, dose, and follow-up duration. Semaglutide demonstrated superior weight loss over liraglutide in head-to-head comparisons, while tirzepatide showed the greatest overall weight reduction. Glycemic improvements were most pronounced in patients with persistent or recurrent type 2 diabetes. Adverse events were predominantly gastrointestinal and mild-to-moderate in severity. Conclusion, GLP-1 RAs are effective and well-tolerated adjuvant therapies following bariatric surgery. Tirzepatide and semaglutide appear to offer greater weight loss benefit compared to liraglutide. Individualized agent selection based on patient characteristics and tolerability is recommended. Prospective randomized trials with standardized outcome reporting are needed to establish definitive clinical guidelines.